Analisis Pengelolaan Piutang dan Mitigasi Risiko untuk Meningkatkan Kolektibilitas Piutang Usaha: Studi Kasus pada PT NWI - Nasywa Rahadatul Aisyi; Hastuti Hastuti (Indonesian Accounting Literacy Journal, 2026)
This study aims to analyze the risks affecting accounts receivable collectability and evaluate the risk mitigation strategies implemented by PT NWI. The study was motivated by the presence of overdue receivables that may affect cash flow and operational sustainability. A qualitative case study approach was employed through interviews, observations, and document analysis. The results indicate that the main risks include delayed customer payments, delays in invoice issuance, administrative errors, system disruptions, and inadequate monitoring of receivables. These risks contribute to delayed cash inflows, increased receivable aging, and reduced collectability. PT NWI has implemented several mitigation strategies, including client assessment, project and receivable monitoring, periodic payment follow-ups, and milestone-based payment arrangements. However, the existing mitigation measures have not fully improved receivable collectability. Therefore, improvements are recommended through the implementation of credit scoring, standardized billing procedures, allowance policies for doubtful accounts, and an integrated receivable monitoring system. This study contributes to the literature by providing an overview of accounts receivable management and risk mitigation strategies in the technology services sector to improve receivable collectability. However, the findings are limited to a single company and focus specifically on accounts receivable management and risk mitigation, limiting their broader generalizability.